The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1590/s0103-84782000000200017
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between passive immunity and morbidity and weight gain in dairy cattle

Abstract: SUMMARY Serum samples from 87 calves from a dairy herd in Southern Brazil were collected to determine the levels of passive transfer and its relationship to morbidity and mean daily weight gain (MDG). Serum immunoglobulin (Ig

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…In contrast, it appears that infection with respiratory diseases or enteric and respiratory together diseases was associated with the passive immune status at 24 to 36 h of age. The results of this study were in agreement with other studies (Moraes et al, 2000;Furman-Fratczak et al, 2011;Marcato et al, 2018) where no association could be found between passive immunity status at 24 to 36 h of age and morbidity attributable to diarrhea. IgG is probable more influential in preventing diarrhea when acting locally in the gastrointestinal tract.…”
Section: The Relationship Between Serum Igg Levels and Morbidity Ratesupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, it appears that infection with respiratory diseases or enteric and respiratory together diseases was associated with the passive immune status at 24 to 36 h of age. The results of this study were in agreement with other studies (Moraes et al, 2000;Furman-Fratczak et al, 2011;Marcato et al, 2018) where no association could be found between passive immunity status at 24 to 36 h of age and morbidity attributable to diarrhea. IgG is probable more influential in preventing diarrhea when acting locally in the gastrointestinal tract.…”
Section: The Relationship Between Serum Igg Levels and Morbidity Ratesupporting
confidence: 93%
“…The growth rate at an early age has been observed to affect the production ability of adult animals. Moraes et al (2000) reported that calves that had FPT gained less weight than those with normal passive immunity (P<0.05). They reported that insufficient amounts of colostrum resulted in increased mortality rates, more severe diarrhea, and lower weight gain in affected calves.…”
Section: The Relationship Between Serum Igg Levels and Calf Growthmentioning
confidence: 98%
See 1 more Smart Citation
“…A similar prevalence (42.9%) has been observed in healthy calves, whereas a distinctly higher prevalence of FPT (97.2%) was found in calves with neonatal diarrhea in previous studies performed in the same geographic region. Others have observed lower (16–28%) or similar (41%) prevalence for FPT. Colostrum of poor quality was the main risk factor associated with FPT in our study.…”
Section: Discussionmentioning
confidence: 89%
“…Higher Ig levels indicate proper maternal protection of calves. Moraes et al (2000) estimated the level of passive transfer in calves using a turbidity test and established that FPT occurs in calves with a serum Ig concentration <5 g/L. In contrast to research in foals, partial failure of passive transfer (PFPT) is rarely described in calves and is likely underestimated in practice.…”
Section: Introductionmentioning
confidence: 99%